(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article explores effective tools and techniques for teaching multilingual students, highlighting the importance of linguistic diversity and cultural sensitivity in education. By examining various strategies and resources, educators can better support the language development and academic success of multilingual learners.